Specific Combinations of Erythrocyte Group Antigens in Blood Donors - Tsintsadze, I. (Indian J Hematol Blood Transfus, 2019)
Blood groups are inherited biological characteristics that do not change throughout life only in healthy people. Blood group antigens determine the adaptation of a human, as a biological species, to the surrounding environment. Our goal was to study the combination and frequency characteristics of three group systems (ABO, RH, KELL) in blood donors. The blood of 743 donors (aged ≥ 18 years) has been investigated on erythrocyte blood group antigens (521 male and 222 female). The sample has been provided from diagnostic laboratory of “Health Centre Medina Ltd” of Batumi. Research was agreed with hematology department of the clinic. Blood typing of the sample has been carried out on the basis of immunogenetic laboratory of Batumi Shota Rustaveli State University. The express method with universal mono-clone antibodies was used in order to reveal blood group system antigens. ABO blood group are distributed the following order: O > A > B > AB. We allocated 16 phenotypic groups. O, Rh+, K− (38.62 ± 1.7%) are represented with the highest percentage among donors and a rather large number of the investigated donors (287 donors) is the carrier of this phenotype. A frequency distribution of the A, Rh+, K− phenotype group 10% (28.93 ± 1.6) was less. 215 donors carry A, Rh+, K− phenotype combination. O, Rh+, K+ and A, Rh+, K+ variations of the phenotype are represented with an equal percentage (3.23 ± 0.4%). 7.94 ± 0.9% donors are characterized by features of the O, Rh−, K− Erythrocyte group. A frequency distribution of B, Rh+, K− phenotype is slightly less − 6.86 ± 0.9%. A, Rh−, K combination of phenotype occurs with a frequency of 4.97 ± 0.7%, and AB, Rh+, K− occurs with a frequency of 2.28 ± 0.5%. I n the donor population there were only single cases of B, Rh−, K+ (0.13 ± 0.01); AB, Rh+, K+ (0.13 ± 0.01); AB, Rh−, K− (0.40 ± 0.2); B, Rh+, K+ (0.26 ± 0.1); O, Rh−, K+ (0.40 ± 0.2); A, Rh−, K+ (0.67 ± 0.2) combination of phenotype. The phenotype AB, Rh−, K+ was not identified. The existence of this database will increase the safety level of transfusion, widen donors database and allow the clinics to find quickly the rare combination of blood group for transfusion and decrease of the risk of post-transfusion complications.